PROSES BELAJAR SISWA SEKOLAH DASAR SELAMA WABAH COVID-19 - Lena, Mai Sri (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
This research aimed to discover the learning process of elementary school students during the Covid-19 outbreak, this includes problems faced by parents and students, and strategies to overcome these problems as well as suggestions for improving online learning in elementary schools. Data were collected through a survey method by distributing questionnaires about the responses of parents on the process of implementing online learning during the covid-19 outbreak. The results of the survey showed that online learning for elementary school students is less conducive, less effective, and less efficient compared to face-to-face learning interaction. This study enriches the research and knowledge related to online learning at primary school during the COVID-19 outbreak.